Stability, Boundedness, and Lagrange Stability of Fractional Differential Equations with Initial Time Difference - Cicek, Muhammed; Yakar, Coskun; Ogur, Bulent (Hindawi Publishing Corporation, 2014)
Differential inequalities, comparison results, and sufficient conditions on initial time difference stability, boundedness, and Lagrange stability for fractional differential systems have been evaluated.
Keywords: Criteria; Systems